General Functionalization Method for Synthesis of α‐Functionalized Polymers by Combination of Anionic Polymerization and Hydrosilation Chemistry. Issue 1 (22nd January 2013) - Quirk, Roderic P.; Chavan, Vijay; Janoski, Jonathan; Yol, Aleer; Wesdemiotis, Chrys; Teck Lim, Goy
Abstract A new general functionalization method (GFM) of synthesizing α‐functionalized polymers has been developed. α‐Vinyl‐functionalized polystyrene was obtained by anionic polymerization of styrene using 4‐pentenyllithium as an initiator. Chloromethyldimethylsilane‐functionalized polystyrene was successfully synthesized from vinyl‐functionalized polystyrene by hydrosilation using Karstedt's catalyst. Nucleophilic substitution of this polymer was carried out in presence of pyrrolidine to obtain α‐pyrrolidine‐functionalized polystyrene. α‐Triethoxysilylpolystyrene was obtained by hydrosilation of a‐4‐pentenylpolystyrene with triethoxysilane using Karstedt's catalyst.